Weight loss and wrestling training: effects on nutrition, growth, maturation, body composition, and strength - Roemmich, J. N.; Sinning, W. E. (Journal of Applied Physiology, 1997)
Adolescent wrestlers (n = 9, 15.4 yr) and recreationally active control adolescent males (n = 7, 15.7 yr) were measured before, at the end (late season), and 3.5-4 mo after a wrestling season to assess the influence of dietary restriction on growth, maturation, body composition, protein nutrition, and muscular strength. Controls consumed adequate amounts of energy, carbohydrate (CHO), protein, and fat, and demonstrated normal gains in weight, fat mass (FM) and fat-free mass (FFM). Wrestlers consumed a high-CHO (61 +/- 2% kcal), low-fat (24 +/- 2% kcal) diet during the season but did not consume adequate energy (24.7 +/- 3.5 kcal.kg-1.day-1) or protein (0.9 g.kg-1.day-1). Deficient dietary intake reduced prealbumin levels (26.0 +/- 1.9 vs. 20.2 +/- 0.9 mg/dl) and slowed the accrual of lean arm and thigh cross-sectional muscle areas (AXSECT, TXSECT, respectively). For wrestlers, dietary deficiency also decreased weight (60.3 +/- 3.5 to 58.0 +/- 3.3 kg), relative fat (9.9 +/- 0.5 to 8.0 +/- 0.7%), and FM (6.0 +/- 0.5 to 4.7 +/- 0.6 kg). Postseason, wrestlers and controls consumed similar diets, and wrestlers had significant increases in prealbumin, AXSECT, and TXSECT. Wrestlers also increased their weight (6.1 +/- 0.6 kg), FFM (3.0 +/- 0.6 kg), and FM (3.2 +/- 0.5 kg) postseason. Rates of bone maturation and segmental growth were not different between the groups. The wrestlers had reductions in elbow and knee strength from preseason to late season but increases postseason. Lean tissue changes were associated with the changes in strength and power (r = 0.72-0.91, P < 0.001). After covariance for FFM or limb-specific cross section, few significant changes remained. In conclusion, dietary restriction reduced protein nutrition and muscular performance but produced little effect on linear growth and maturation. Prealbumin levels and the rate of lean tissue accrual were positively related (r = 0.43, P < or = 0.05).